The Role of Quality of Governance in Reducing Pollution in Romania: An ARDL and Nonparametric Bayesian Approach - Simionescu, Mihaela; Neagu, Olimpia; Gavurova, Beata (Frontiers in Environmental Science, 2022)
Achieving global sustainability and greener growth goals represents a challenge for all countries, especially developing ones. The quality of institutional framework of a country and its effectiveness determines the levels of environmental control and sustainability. Since pollution reduction is an objective for European environmental policies, Romania should achieve this goal taking into account the quality of governance. In this paper, the impact of Worldwide Governance Indicators on the greenhouse gas emissions is assessed for Romania in the period 1996-2019 using autoregressive distributed lag models. The results indicate that control of corruption, political stability and regulatory quality reduced pollution in the long-run, while voice and accountability contributed to greenhouse gas emissions growth. Renewable energy consumption did not reduce pollution in the short and in the long-run in the period 1996-2019, while the analysis made for 2007-2019 suggested the significant contribution of renewable energy consumption in reducing pollution. The analysis based on Bayesian ridge regressions after Romanian joined the European Union indicated that control of corruption and political stability reduced the level of pollution. Policy implications of these results are widely discussed.